2001
DOI: 10.1097/00002480-200109000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Inferior Vena Cava Diameter as a Marker of Dry Weight in Nonoliguric Hemodialyzed Patients

Abstract: We have previously reported that the maximal inferior vena cava (IVC) diameter during quiet expiration (IVCe) measured by ultrasonography correlates well with the amount of body fluid, especially the circulating blood volume(2) and proposed using the criteria of IVC diameter to determine dry weight (DW) in anuric hemodialyzed (HD) patients: standard IVCe of pre- and post-HD are 14.9 +/- 0.4 and 8.2 +/- 0.3 mm, respectively (1). However, the same post-HD IVC criterion should not be applied to nonoliguric HD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…9 Previous attempts at noninvasive hemodynamic monitoring using plethysmography, thoracic electrical bioimpedance, and external Doppler probes have shown these methods to be cumbersome or inaccurate. [10][11][12][13] Other investigators have used echocardiography 14,15 and handheld ultrasound 16 to image the diameter of the inferior vena cava in order to assess intravascular volume status, but these techniques require expertise in sonographic imaging. An alternative technique is to measure peripheral venous pressure, which correlates with CVP.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous attempts at noninvasive hemodynamic monitoring using plethysmography, thoracic electrical bioimpedance, and external Doppler probes have shown these methods to be cumbersome or inaccurate. [10][11][12][13] Other investigators have used echocardiography 14,15 and handheld ultrasound 16 to image the diameter of the inferior vena cava in order to assess intravascular volume status, but these techniques require expertise in sonographic imaging. An alternative technique is to measure peripheral venous pressure, which correlates with CVP.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47][48] IVC dimensions, as measured by US, have been shown to provide useful information about right atrial pressure and baseline blood volume in patients who undergo hemodialysis. 49,50 In a study of adult volunteers before and after blood donation, measurement of IVC diameter was noted to be a reliable indicator of blood loss. 51 We are not aware of any previous data from the pediatric emergency medicine literature addressing the role of BLEEP.…”
Section: Discussionmentioning
confidence: 99%
“…To address these shortcomings, much research effort has been expended on the search for an objective measurement of fluid status that provides a common standard against which patients may be compared (1,2,6). Blood volume monitoring (2,7), ultrasound assessment of inferior vena cava diameter (2,8), and several biochemical parameters, such as brain or atrial natriuretic peptide (9), have been shown not to give an accurate estimate of DW (1,2). For more than 20 yr, bioelectrical impedance analysis (BIA) has been recognized as a noninvasive and simple technique to measure body hydration status of patients and has gained much attention for the determination of DW in HD patients (10 -13).…”
mentioning
confidence: 99%